Women’s participation in agricultural cooperatives in Ethiopia - Woldu, Thomas; Tadesse, Fanaye; Waller, Marie-Katherine (International Food Policy Research Institute, 2013)
This paper uses a rich dataset from a survey undertaken by the Ethiopian Economic Association (EEA) and the Interna-tional Food Policy Research Institute (IFPRI) in 2009 in eight woredas in seven regions of Ethiopia with a sample of 1,117 households and 73 agricultural cooperatives. Using descriptive statistics and econometric analysis under a critical gender lens, the paper identifies which cooperative, household, and individual level characteristics influence women’s participation in agricultural cooperatives. The findings suggest that a major barrier to women’s access are gender biases within households, communities, and cooperatives themselves that favor educated male household heads and land owners over resource-poor women.